DAMPAK PROGRAM PENGEMBANGAN DIRI PADA PERTUMBUHAN PRIBADI DAN PERTUMBUHAN PROFESIONAL PADA PT ATI TRASINDO - Ayu Lucy Larassaty; Nur Layli Fatikhatun Nisa; Sherly Amalia Fernanda (Pusat Riset dan Inovasi Nasional, 2023)
Self-development is a process that aims to improve individual ability to face challenges and achieve life goals. Workplace self-development programs are becoming increasingly popular as a strategy to increase employee performance and motivation. This study aims to evaluate the impact of self-development programs on individual personal and professional growth. The samples taken are employees who work at PT Ati Transindo located in Sidoorjo. Sampling was carried out by purposive sampling technique with predetermined criteria. This study aims to evaluate the impact of self-development programs on individual personal and professional growth. The study was conducted by collecting data from employees at PT Ati Trasindo for a certain period. Data was collected through interviews and distributing questionnaires at PT Ati Trasindo. The results showed that the self-development program did not have a significant positive effect on the personal and professional growth of the participants. Participants reported improvements in communication, leadership, time management, and decision-making skills. In addition, this program also affects job satisfaction and motivation. These findings suggest that self-development programs can be an effective strategy in enhancing individual personal and professional growth in the workplace